Inggris - Abdul Ghoni; Erny Arianty (ITB AAS INDONESIA Surakarta, 2026)
This research examines the impact of policy guarantees on the Sharia insurance industry in Indonesia, focusing on analyzing the factors causing claim payment failures by insurance companies and the roles of the Financial Services Authority (OJK) and the Deposit Insurance Corporation (LPS) in addressing these issues. The research employs SWOT analysis to identify the strengths, weaknesses, opportunities, and threats in the policy guarantee program. The findings suggest that policy guarantees can enhance customer trust and the stability of the Sharia insurance industry, although challenges remain such as incomplete regulatory support and low levels of public education. The policy guarantee program can be an aggressive growth strategy for the Sharia insurance industry by leveraging existing strengths and opportunities, while mitigating weaknesses and threats. This research contributes by providing insights into the importance of policy guarantees as a tool for improving customer protection and promoting the development of the Sharia insurance industry in Indonesia.